Running gait modifications can lead to immediate reductions in patellofemoral pain - Esculier, Jean-Francois; Bouyer, Laurent J.; Roy, Jean-Sébastien (Frontiers in Sports and Active Living, 2023)
Gait modifications are commonly advocated to decrease knee forces and pain in runners with patellofemoral pain (PFP). However, it remains unknown if clinicians can expect immediate effects on symptoms. Our objectives were (1) to compare the immediate effects of gait modifications on pain and kinetics of runners with PFP; (2) to compare kinetic changes in responders and non-responders; and (3) to compare the effects between rearfoot strikers (RFS) and non-RFS. Sixty-eight runners with PFP (42 women, 26 men) ran normally on a treadmill before testing six modifications: 1- increase step rate by 10%; 2- 180 steps per minute; 3- decrease step rate by 10%; 4- forefoot striking; 5- heel striking; 6- running softer. Overall, there were more responders (pain decreased ≥1/10 compared with normal gait) during forefoot striking and increasing step rate by 10% (both 35%). Responders showed greater reductions in peak patellofemoral joint force than non-responders during all conditions except heel striking. When compared with non-RFS, RFS reduced peak patellofemoral joint force in a significant manner (P<0.001) during forefoot striking (partial η2=0.452) and running softer (partial η2=0.302). Increasing step rate by 10% reduced peak patellofemoral joint force in both RFS and non-RFS. Forty-two percent of symptomatic runners reported immediate reductions in pain during ≥1 modification, and 28% had reduced pain during ≥3 modifications. Gait modifications leading to decreased patellofemoral joint forces may be associated with immediate pain reductions in runners with PFP. Other mechanisms may be involved, given that some runners reported decreased symptoms regardless of kinetic changes.